Fracture toughness of iron and copper powder compacts using modified diametrical compression test technique - Akoredeley, Alabi Abdulmumin (2018)
In the industries today, metal components are increasingly being produced by powder metallurgy (PM) method. The PM method is highly efficient in cost of production and materials usage. However, PM components suffer from inhomogeneous density variation and are more likely to have internal cracks. These deficiencies usually make PM components prone to sudden fracture failure. A parameter that is known to define the rate at which cracks grow in a material is fracture toughness. Unfortunately, the fracture toughness of most metal powder compacts have not been determined due to lack of suitable test technique. This study developed a notching device that has the capability to provide uniform notches on the surfaces of powder compacts. The effectiveness of the notching device enhanced the determination of mode I fracture toughness (KIC) of two metal powder compacts; iron and copper. A method known as the modified diametrical compression test technique (MDCTT) was also developed to measure the mode II fracture toughness (KIIC) of the powder compacts. Finally, the study examined the influence of density on the rate of crack propagation in the compacts and developed mathematical relation that predicts fracture toughness from the relative density of either the iron or copper powder compacts. Notched samples of two types of metal powder; Hoaganas ASC100.29 iron powder and pure copper powder were prepared by uniaxial compaction in a rigid die using universal testing machine. The relative density of the powder compacts was determined as a fraction of the density of the compact to their corresponding solid metal before the diametrical compression test was carried out for each sample. The behavior of the cracks around the tip of the notch was examined using scanning electron microscope (SEM). A new equation was developed to calculate the values of KIIC from the MDCTT. The results of KIC for the iron powder compacts showed close agreement with values mentioned in the literature. The KIC values for copper powder compacts range from 0.32 to 0.58 MPa.m0.5 while the KIIC for the iron and copper powder compacts ranged from 0.30 to 0.57 MPa.m0.5 and 0.28 to 0.59 MPa.m0.5 respectively. The ratio KIIC/KIC for the iron and copper powder compacts from this study showed good agreement with the predicted values of 0.87 and 1.04 based on the maximum tangential stress (MTS) and the minimum strain energy density (SED) criteria respectively. The agreement implies that the developed MDCTT is reliable and can be used to measure the KIIC of other metal powder compacts. Furthermore, the results also show that the rate of crack extension reduced as the density of the powder compacts increases. A generalized mathematical expression that relates fracture toughness and relative density has been successfully developed. This relationship will be beneficial for further analysis of crack propagation within metal powder compact.